Question
upstudy study bank question image url

EXERCISE 5.1 Calculate the following products and leave the answers in exponential form. 1. a) \( 3^{5} \times 3^{5} \) \( \begin{array}{ll}\text { c) } 15^{4} \times 15^{1} \times 15^{7} & \text { b) } 2^{6} \times 2^{2} \times 2^{3} \\ \text { 2. } a)(-3)^{2} \times(-3)^{3} & \text { d) } 10^{9} \times 10^{11} \times 10^{10} \\ \text { c) }(-a)^{5} \times(-a)^{3} \times(-a) & \text { b) } a^{4} \times a^{6} \times a^{8} \\ \text { a) } 4 a^{2} \times 5 a & \text { d) } y^{7} \times(-y)^{6} \\ \text { c) } a^{2} b^{2} \times a^{3} b^{6} & \text { b) } 8 a^{2} \times-2 a^{3}\end{array} \)

Ask by Olson Li. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the simplified answers in exponential form: 1. a) \( 3^{10} \) b) \( 2^{11} \) c) \( 15^{12} \) 2. a) \( (-3)^{5} \) b) \( a^{18} \) c) \( (-a)^{9} \) d) \( y^{13} \) 3. a) \( 20a^{3} \) b) \( -16a^{5} \) c) \( a^{5}b^{8} \) d) \( 10^{30} \)

Solution

Below are one acceptable set of answers. In each case we use the rule that when multiplying like bases you add exponents. ────────────────────────────── 1. Using numeric bases:  a)  3⁵ × 3⁵    = 3^(5+5)    = 3¹⁰  b)  2⁶ × 2² × 2³    = 2^(6+2+3)    = 2¹¹  c)  15⁴ × 15¹ × 15⁷    = 15^(4+1+7)    = 15¹² ────────────────────────────── 2. Using negative bases and variables:  a)  (–3)² × (–3)³    = (–3)^(2+3)    = (–3)⁵  b)  a⁴ × a⁶ × a⁸    = a^(4+6+8)    = a¹⁸  c)  (–a)⁵ × (–a)³ × (–a)¹    = (–a)^(5+3+1)    = (–a)⁹  d)  y⁷ × (–y)⁶    Notice that (–y)⁶ = (–1)⁶·y⁶ = y⁶ because (–1)⁶ = 1.    Thus, y⁷ × y⁶ = y^(7+6)    = y¹³ ────────────────────────────── 3. Mixing numerical coefficients and variables:  a)  4a² × 5a    = (4×5)·(a²×a¹)    = 20a^(2+1)    = 20a³  b)  8a² × (–2a³)    = (8×–2)·(a²×a³)    = –16a^(2+3)    = –16a⁵  c)  a²b² × a³b⁶    = (a^(2+3))·(b^(2+6))    = a⁵b⁸  d)  10⁹ × 10¹¹ × 10¹⁰    = 10^(9+11+10)    = 10³⁰ ────────────────────────────── Each answer is left in exponential form as requested.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

Let's dive into these calculations using the laws of exponents! 1. a) \( 3^{5} \times 3^{5} = 3^{5+5} = 3^{10} \) 1. b) \( 2^{6} \times 2^{2} \times 2^{3} = 2^{6+2+3} = 2^{11} \) 1. c) \( 15^{4} \times 15^{1} \times 15^{7} = 15^{4+1+7} = 15^{12} \) 2. a) \( (-3)^{2} \times (-3)^{3} = (-3)^{2+3} = (-3)^{5} \) 2. b) \( a^{4} \times a^{6} \times a^{8} = a^{4+6+8} = a^{18} \) 2. c) \( (-a)^{5} \times (-a)^{3} \times (-a) = (-a)^{5+3+1} = (-a)^{9} \) 2. d) \( 10^{9} \times 10^{11} \times 10^{10} = 10^{9+11+10} = 10^{30} \) Now for the additional products: 2. a) \( 4 a^{2} \times 5 a = 20 a^{2+1} = 20 a^{3} \) 2. b) \( 8 a^{2} \times -2 a^{3} = -16 a^{2+3} = -16 a^{5} \) 2. c) \( a^{2} b^{2} \times a^{3} b^{6} = a^{2+3} b^{2+6} = a^{5} b^{8} \) 2. d) \( y^{7} \times (-y)^{6} = y^{7} \times (-1)^{6} y^{6} = y^{7} \times 1 \times y^{6} = y^{7+6} = y^{13} \) Here are the final results in exponential form: 1. a) \( 3^{10} \), 1. b) \( 2^{11} \), 1. c) \( 15^{12} \), 2. a) \( (-3)^{5} \), 2. b) \( a^{18} \), 2. c) \( (-a)^{9} \), 2. d) \( 10^{30} \), 2. a) \( 20 a^{3} \), 2. b) \( -16 a^{5} \), 2. c) \( a^{5} b^{8} \), 2. d) \( y^{13} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy